penggunaan penggunaan teori clive bell pada gambar khas spanduk pecel lele, asal kabupaten Lamongan, Jawa Timur - Billah, Daniyatu; Ismurdiyahwati, Ika (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2024)
Clive Bell is a philosopher of modern classical art who is famous for his idea of ​​significant form. Bell is a philosopher who was influenced by Plato's line of thought about beautiful forms that seem to be outside the form of the work itself. According to him, all aesthetic systems start from the subject's personal experience of the occurrence of typical emotions. There are three theories of Clive Bell, namely aesthetic emotion, meaningful form, and essentialism. This research uses a qualitative research approach with data collection stages as the completion material for this research, because qualitative methods generally emphasize analysis or descriptiveness. Data can be obtained from data collection techniques in the form of in-depth interviews and observation. Based on the analysis carried out, a new meaning emerged in the typical image from pecel lele’s banner. The typical image pecel lele’s banner is not just an ordinary banner without any artistic value in it. After carrying out this research, it was found that in the typical image pecel lele’s banner there are Clive Bell's principles, namely aesthetic emotions; as sales identity, meaningful forms; as a memorable image, and essentialism; the typical image as identification and there are also principles of painting such as color lines, shapes, planes, and textures.